Genomic insights from the Squalius alburnoides complex in the confined Quarteira drainage population: what's new? - Nabais, Catarina Antunes Angélico Pinto, 1988- (2011)
Tese de mestrado. Biologia (Biologia evolutiva e do Desenvovimento). Universidade de Lisboa, Faculdade de Ciências, 2011